AN ANALYSIS OF SPEECH ACTS IN MERRY RIANA: MIMPI SEJUTA DOLLAR MOVIE - Sumaniari, Ni Wayan Rosi; Ramendra, Dewa Putu; Mahendrayana, Gede (Universitas Pendidikan Ganesha, 2021)
People rarely know the function of the language used in the film. This study analyzes speech acts in a dialogue film entitled Merry Riana: Dreams of a Million Dollars. This research is a qualitative descriptive study. Data were analyzed from the form of speech acts consisting of direct and indirect speech acts in the form of declarative, imperative, and interrogative. The type of speech act analysis uses Searle's theory of representative, directive, commissive, expressive, and declaration. The result of this research is that direct speech act in interrogative form is 43.63%. Direct speech acts in the declarative form are 95 (43.18%), direct speech acts in the imperative form are 24 (10.90%), indirect speech acts in the imperative form are 2 (0.9%), indirect speech acts in imperative form as much as 2 (0.9%). interrogative form is 2 (0.9%), and indirect speech act in declarative form is 1 (0.45%). Furthermore, 74 utterances are analyzed into five types of speech acts. The most dominant representative used 36 (48.6%). Then followed by directive 21 (28.3%), expressive 14 (18.9%), commissive 3 (4.0%), and declarative 0 (0.0%). This research implies that understanding speech acts plays an important role in communication.